(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: This article addresses the question of the inter-company cooperation’s weakness within the Algerian date palm sector. Through a field survey of several companies producing and exporting dates, we establish an exploratory diagnosis of the state of inter-company cooperation and we suggest ways to improve the effects of this cooperative process on export performance. Thus, the objective of this article is to explain, in the light of the internationalization approaches theories and in particular the territorial approach, why small Algerian companies exporting dates do not engage in a cooperative and innovative process, especially since their small size greatly limits their ability to penetrate new external markets. Keywords: Governance, territories, export, date sector, performance.